KAJIAN TOPONIMI KAMPUNG-KAMPUNG PRAJURIT KERATON YOGYAKARTA: KAITANNYA DENGAN PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) - NFN Sudaryanto (Balai Bahasa Kalimantan Barat, 2018)
The Keraton Yogyakarta (Yogyakarta Palace) has 10 soldiers whose names are different. Among them, Bugis Soldiers, Surakarsa Soldiers, Mantrijero Soldiers, Ketanggung Soldiers, Nyutra Soldiers, Prawiratama Soldiers, Jagakarya Soldiers, Patangpuluh Soldiers, Dhaeng Soldiers, and Wirabraja Soldiers. Each soldier’s name became the name of the village/hamlet in the City of Yogyakarta today. This toponimi study focuses on the names of the villages of the Yogyakarta Palace. Viewed from the origin of the language, the names of the village came from Sanskrit, Bugis, and Kawi. Insight into the names of the Yogyakarta Palace village is useful for foreign speakers who are learning the language and culture of Indonesia (BIPA), especially in Yogyakarta. They can learn the origin of the names of the villages, and compare them with other regions in Indonesia, such as in West Java and DKI Jakarta and surronding areas.